2017
DOI: 10.1007/s40520-017-0740-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feedback-based balance and core resistance training vs. Pilates training on cognitive functions in older women with mild cognitive impairment: a pilot randomized controlled trial

Abstract: Findings suggest that non-aerobic training should be further explored as a beneficial intervention for older adults suffering from MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 8 publications
0
57
0
4
Order By: Relevance
“…The detailed characteristics of 19 included studies [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42] are provided in Table 1. Fifteen studies [25,27,28,29,30,31,32,33,34,35,36,37,38,39,42] had only one control group, and the remaining studies [24,26,40,41] involved two or three control groups. Thus, 24 independent effect sizes were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed characteristics of 19 included studies [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42] are provided in Table 1. Fifteen studies [25,27,28,29,30,31,32,33,34,35,36,37,38,39,42] had only one control group, and the remaining studies [24,26,40,41] involved two or three control groups. Thus, 24 independent effect sizes were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The participants’ mean age ranged from 60 to 84 years, and some of them had diseases such as cognitive impairment, stroke and depression. Tai Chi, Yoga, Qigong and Pilates programs were employed in twelve [24,25,27,28,29,33,36,37,39,40,41,42], four [26,31,32,35], two [34,38] and one [30] studies, respectively. The duration of intervention ranged from 8 to 52 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, physical exercise has been demonstrated to be an effective nonpharmacologic strategy for combating cognitive decline and hippocampal degeneration in the cognitively healthy elderly [1] , [2] , [3] , [4] , [5] and in those with genetic risk for AD [6] . Similarly, converging evidence demonstrated the benefits of practicing aerobic, resistance, or balance training on cognition [7] , [8] , [9] and hippocampal volume increase [10] in aMCI subjects.…”
Section: Introductionmentioning
confidence: 93%
“…In the study of Iuliano et al (2015) elderly people underwent 12 weeks of resistance training with 50% of one repetition maximum (RM) intensity and no alterations on inhibitory control or selective attention were observed. In contrast, Jurakic et al (2017) demonstrated that three sessions of resistance training (75% of 1RM) per week improved inhibitory control in elderly women. Opposing from those findings, Weinberg et al (2014) found that memory was improved in a single session of resistance training for young adults (men and women), performed at 10 maximum repetition zone.…”
Section: Introductionmentioning
confidence: 83%